THE PLACE OF HISTORY IN NATIONAL INTEGRATION AND DEVELOPMENT: THE KENYAN PERSPECTIVE - Kiprono, Chebii Zephaniah (Journal of Historical Studies, 2020)
History as both a discipline and a concept is intertwined with the direction that any society takes. There is a positive link between progress of a society and its integration. These are best achieved through the inculcation of historical values and heritage; indeed, the best way of moving forward is by looking back at history. Therefore, this paper examines the place of history in national integration and development specifically with regards to Kenya. It posits that history, as one of the subjects taught in Kenya's education system, is critical in promoting political, social and economic development. This is because it provides an in depth understanding and appreciation in individuals about where the society has come from, the challenges it has faced and out of that, the best way of solving those challenges. All these values form a momentum which is capable of promoting progress. The study used desk review by collecting, organizing and synthesizing available information which included journal articles, reports and newspaper focusing on the subject of history. For a better understanding of the nature of forces and processes of national development, there is need to appreciate the diversity that makes up Kenya. Thus, through the teaching and study of history, individuals can inculcate national consciousness, patriotism and sense of social responsibility in their lives. Certain historical values that the discipline transmits like cohesion, inter-ethnic relations and cultural diffusion should form the basis of national orientation, instead of a debate on deprivation, resource control and other mischievous issues that stunt development. This article concludes that since development is a product of change, and the subject matter of history focuses on continuity and change, it follows that development can only be understood and appreciated within the context of history. It is this strategic place of history in facilitating integration that makes history incubator of development.